Mysticism and Visual Theology: The Sacred Image and Gaze in Saint Teresa of Ávila - Onofre, Dario Velandia (Journal of medieval religious cultures, 2025)
Given the immense complexity contained in the literature and testimonies of a crucial age in the consolidation of the Catholic reform, Saint Teresa of Ávila’s literary works have been studied from many perspectives. Nonetheless, the possible relationship between a mystical theology and a visual theology has not been given sufficient attention. The present article intends to demonstrate how the Saint’s books helped consolidate a theology of visual practices that defends the power of sacred images and the sacred gaze.